Pengaruh Ukuran Perusahaan, Profitabilitas dan Kinerja Lingkungan terhadap Pengungkapan Emisi Karbon - Arsy, Chanyndita Bivothy; Amin, Muhammad Nuryatno (Ekonomis: Journal of Economics and Business, 2025)
This research aims to analyze the influence of company size, profitability and environmental performance on carbon emissions disclosure in Basic Materials sector companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The data used is secondary data obtained from the Indonesian Stock Exchange. The sampling technique used purposive sampling, totaling 114 samples. The data analysis technique was carried out using multiple regression analysis. The research results show that company size and profitability have no effect on carbon emissions disclosure, but environmental performance has a positive effect on carbon emissions disclosure in Basic Materials sector companies listed on the Indonesia Stock Exchange during the 2020-2022 period.